Socioeconomic, Dietary and Health Determinants of Body Composition in Haitian School Children Aged 3–13 Years (P11-130-19). (13th June 2019) - Musonza, Clive; Dulience, Sherlie Jean-Louis; Delnatus, Jacques Raymond; Wolff, Patricia; Nagar, Aishwarya; Chapnick, Melissa; Iannotti, Lora
Abstract: Objectives: This study aimed to characterize socioeconomic, dietary and health factors associated with body composition of school-aged children in Cap-Haïtien, Haiti. Methods: Baseline data from a cluster randomized controlled trial of children aged 3–13 years (n = 1084) to test the effectiveness of lipid-based nutrient supplement on anemia and other nutrition outcomes was used for this analysis. Anthropometric measures of height and weight were collected from the children using standard WHO protocols. Parent surveys provided information on household-level socioeconomic and demographic information and frequency of dietary intakes and infectious disease morbidities of the children. Body composition was determined using bioelectric impedance analysis (BIA). Equations, validated using deuterium dilution method in Gambian school children, were then used to derive fat mass (FM) and fat free mass (FFM). Multiple linear regression modeling identified factors associated with body composition. Results: There were 43.7% of children categorized as moderately thin (body mass index (BMI) z score < -1). Mean percentage of FM was 7.8% (SD ± 3.5) and 11.9% (SD ± 4.9) while mean FM (kg) was 1.7kg (SD ± 0.8) and 3.1kg (SD ± 3.5) for thin children and those not thin, respectively. Child's age, ear infection in the last month and bread consumption were negatively associated with FM (%), whereas child's sex, maternal BMI, and toilet type used showed a positive relationship. FM (kg) was positively associated with child's age, sex, height-for-age z score, maternal BMI, house ownership and toilet type used. Models 1, 2, and 3 with BMI z score, FM (%) and FM (kg) as dependent variables respectively showed: [F(6, 773) = 16.2, β = –1.5, P < .001, (Adj. R2 = .11)], [F(6, 747) = 42.2, β = 2.7, P < .001, (Adj. R2 = .25)] and [F(6, 746) = 36.0, β = -2.7, P < .001, (Adj. R2 = .22)]. Conclusions: This study provides evidence of socioeconomic, dietary and health factors associated with body composition in Haitian school-aged children, however more research is required to identify additional factors mediating this relationship. Funding Sources: Supported by the USDA Foreign Agricultural Service Micronutrient Fortified Food Aid Products program FFE-521-2012/034-00, the Masters Research Fellows Program of the Brown School and E3 Nutrition Lab.